(untitled) (American Journal of Management, 2021)
The glass ceiling effect is unfortunately still a reality in academia. Only 30% U.S University has female presidents. Given the multiple benefits of gender diversity in senior management, understanding gender gap in top leadership should be a priority. The purpose of this study was to investigate gender roles and leadership effectiveness in higher education. The results show that female leaders were seen less effective than men when committing relationship mistakes. Additionally, both male and female leaders were seen less effective when committing relationship mistakes than task mistakes. These findings signal the need to examine gender bias across other academic settings.